Penerapan Algoritma Binary Searching Untuk Pencarian Berkas Pada Sistem Pengarsipan (Study Kasus: Pemerintahan Desa Kedungbetik) - Nasruddin, Hammam; Mashuri, Chamdan; Wiratsongko, Radityo (Inovate, 2021)
Archiving files and searching files that are still using manual or not computerized methods. The purpose of this research is to create a website-based filing system that has a file search feature with a fast and accurate time of the many files that have been archived. To find files quickly and accurately from a lot of data, we need an algorithm, the binary searching algorithm. This algorithm is a search algorithm that can search for files in a fast time and has a lighter amount of computing. From the results of testing the search speed using a binary search algorithm, the data search speed test is 100 document archive data, with the name of the data sought is population data. Searching using an algorithm has a time of 148 / ms while searching without using an algorithm is 799 / ms. From testing the search speed using a binary search algorithm this is 95% Keywords: System, Archiving, Algorithm, Binary Searching, File, Searching